Chromatographic determination, decline dynamic and risk assessment of sulfoxaflor in Asian pear and oriental melon. (8th November 2017) - Kabir, Md. Humayun; Abd El‐Aty, A. M.; Rahman, Md. Musfiqur; Chung, Hyung Suk; Lee, Han Sol; Kim, Sung Woo; Chang, Hee‐Ra; Shin, Ho‐Chul; Shin, Sung Shik; Shim, Jae‐Han
Abstract: The dissipation pattern of sulfoxaflor in Asian pear cultivated in an open field conditions and in oriental melon grown under plastic house conditions was each studied in two different locations. Residues in field‐treated samples were determined using liquid chromatography coupled with an ultraviolet detector and confirmed by liquid chromatography–tandem mass spectrometry. A calibration curve for sulfoxaflor was linear over the concentration range 0.1–5.0 mg/L, with a coefficient of determination of 0.9999. The limits of detection and quantification (LOQ) were 0.007 and 0.02 mg/kg, respectively. Recoveries at three fortification levels (LOQ, 10 × LOQ and maximum residue limit) ranged from 70.5 to 86.2%, with a relative standard deviation ≤5.8%. The dissipation half‐lives were 10.8 and 7.9 days in pear and 5.4 and 5.9 days in oriental melon, at sites 1 and 2, respectively. Based on a pre‐harvest residue limit curve, it was predicted that, if the residues at 10 days before harvest in Asian pear are <0.54/0.61 mg/kg and those in oriental melon are <1.43/1.26 mg/kg, then the residue level will be below the maximum residue limit at harvest. Risk assessment at zero days showed a percentage acceptable daily intake of 10.80% in Asian pear and 1.77 and 1.55% in oriental melon, for sites 1 and 2, respectively. These values indicate that the fruits are safe for consumption.